Measuring language development in pervasive developmental disorders (PDD) and non-PDD children - Molly D. Oktarina; Hardiono D. Pusponegoro; Zakiudin Munasir (Indonesian Pediatric Society, 2009)
Background Impairments in language and related socialcommunication skills can be found in children with pervasivedevelopmental disorders (POD) and other developmentallanguage disorders (non-POD). These conditions lead to decisionof enrolling children with language disorders to speech therapydespite that it is not the therapy of choice for POD.Objectives To explore the differences in receptive language, verbal expressive language, and non-verbal expressive language between PDD and non-POD childrenMethods A cross sectional study was performed in October2008 to January 2009. Questionnaire using the MacArthurcommunicative development inventory (CDI) was filled byparents whose children were PDD and non-PDD patients aged 1to 3 years old. The diagnosis ofPDD was based on the diagnosticand statistical manual IV.Results A total of 42 PDD and 42 non-POD subjects wereevaluated. There was significant difference between PDD and nonPOD in receptive language [P= 0.01 (95% CI -170.63 to -24.33)in 12 to 24 month-old subjects and P< 0.01 (95% CI -158.28to -92.99) in > 24 to 36 month-old subjects] and non-verbalexpressive language [P= 0.01 (95% CI -20.96 to -1.96) in 12 to24 month-old subjects and P< 0.01 (95% CI -22.65 to -10.5) in> 24 to 36 month-old subjects]. Verbal expressive language wasnot significantly different between POD and non-POD childrenage 1 to 3 year-old.Conclusions PDD children are more likely to have a delay inreceptive language and non-verbal expressive language compare to non-POD children. Verbal expressive language can not be used to differentiate POD and non-POD children.